Is there a role for PET-CT and SPECT-CT in pediatric oncology?. (November 2013) - Biermann, Martin; Schwarzlmüller, Thomas; Fasmer, Kristine Eldevik; Reitan, Bernt C; Johnsen, Boel; Rosendahl, Karen
During the last decade, hybrid imaging has revolutionized nuclear medicine. Multimodal camera systems, integrating positron emission tomography (PET) or single photon emission computed tomography (SPECT) with computed tomography (CT) now combine the contrast provided by tumor-avid radioactive drugs with the anatomic precision of CT. While PET-CT to a great extent has replaced single-modality PET in adult oncology, the use of PET-CT in children has been controversial, since even the lowest dose CT protocols adds approximately 2 mSv to the radiation dose of about 4 mSv from the PET-study with F-18-fluorodeoxyglucose (F-18-FDG). The article describes the current techniques used, discusses radiation doses and gives an overview of current indications for PET-CT and SPECT-CT in children. Hybrid imaging with a tumor-avid radioactive drug provides extremely high contrast between tumor and background tissues, while the CT component helps to locate the lesion anatomically. Currently both PET-CT and SPECT-CT play a role in pediatric oncology; PET-CT using F-18-FDG particularly for staging and follow-up of lymphoma and brain cancer, bone and soft tissue sarcomas; SPECT-CT with I-123-metaiodobenzylguanidine (MIBG) for tumors of the sympathetic nervous system such as neuroblastoma and pheochromocytoma while the remaining neuroendocrine tumors are imaged with radioactively labeled somatostatin analogues. To reduce radiation dose, a low-dose CT in combination with ultrasound and/or magnetic resonance imaging for the assessment of anatomy is often preferred.